Structure of Coal-Derived Metal-Supported Few-Layer Graphene Composite Materials Synthesized Using a Microwave-Assisted Catalytic Graphitization Process - Islam, Faridul (Nanomaterials (Basel), 2021)
Metal-supported few-layer graphene (FLG) was synthesized via microwave-assisted catalytic graphitization owing to the increasing demand for it and its wide applications. In this study, we quickly converted earth-abundant and low-cost bituminous coal to FLG over Fe catalysts at a temperature of 1300 °C. X-ray diffraction, Raman spectroscopy, transmission electron microscopy, and N(2) adsorption–desorption experiments were performed to analyze the fabricated metal-supported FLG. The results indicated that the microwave-irradiation temperature at a set holding-time played a critical role in the synthesis of metal-supported FLG. The highest degree of graphitization and a well-developed pore structure were fabricated at 1300 °C using a S10% Fe catalyst for 20 min. High-resolution transmission electron microscopy analysis confirmed that the metal-supported FLG fabricated via microwave-assisted catalytic graphitization consisted of 3–6 layers of graphene nanosheets. In addition, the 2D band at 2700 cm(−1) in the Raman spectrum of the fabricated metal-supported FLG samples were observed, which indicated the presence of few-layer graphene structure. Furthermore, a mechanism was proposed for the microwave-assisted catalytic graphitization of bituminous coal. Here, we developed a cost-effective and environmental friendly metal-supported FLG method using a coal-based carbonaceous material.